Testing an artificial aril as a new ant-attractant - Rabello, Ananza Mara; Bernardi, Leopoldo Ferreira de Oliveira; Ribas, Carla Rodrigues (Revista Biociências, 2014)
Ants are attracted by structures called arils, which have different biochemical compositions. In this study, we tested seed removal by ants by offering a new ant-attractant and we analyzed its efficiency to induce seed removal. We installed six observational points observed for 6 h thereafter. We collected 12 ant species removing the ant-attractants. There was a significant difference in the removal of the different types of resources. The new ant-attractant used as artificial aril was significantly more removed than the other types of resources. Therefore this new ant-attractant used as artificial aril will be a useful tool in studies concerned about ant-plant interactions and evaluating ecosystem functions.